ANALISIS EFEKTIVITAS INSTRUMEN MONETER SYARIAH DALAM MENGENDALIKAN INFLASI DI INDONESIA - Mahmud, Prananda Priyandan; Darmawati, Darmawati; Mainata, Dedy (Faculty of Islamic Economics and Business, Sultan Aji Muhammad Idris State Islamic University of Samarinda, 2024)
This study is based on the framework that inflation is one of the main macroeconomic challenges in Indonesia. The objective of this research is to analyze the impact of the Bank Indonesia Sharia deposit facility (FASBIS), reserve requirement (GWM), and Islamic interbank money market (PUAS) on inflation in Indonesia during the 2018-2022 period. A quantitative approach was adopted, utilizing multiple linear regression analysis. Data were collected from the official websites of Bank Indonesia and the Financial Services Authority. The results revealed that, partially, GWM significantly affects inflation, while FASBIS and PUAS show no significant impact. However, simultaneously, the three instruments significantly influence inflation. The main conclusion drawn is that strengthening GWM policies and further developing other Islamic monetary instruments can contribute to inflation stability in Indonesia.